Menguji Ketangguhan Realisme: Kritik terhadap Putusan Mahkamah Konstitusi Nomor 14/PUU-XI/2013 Pasca Pemilu Serentak 2019 - Titon Slamet Kurnia (The Constitutional Court of the Republic of Indonesia, 2022)
This article examines Constitutional Court Decision Number 14/PUU-XI/2013 following the simultaneous elections of 2019. The object is the correctness of the utilisation of realism as a theory of adjudication by the Court in deciding the constitutionality of Law Number 42 of 2008. It can be concluded that, the Court’s decision is false, i.e. it fails to strengthen presidential in Indonesia, as expected by the Court, according to coattail effect theory. Hence, responding to this failure, this article suggests a caveat that the utilisation of realism should anticipate its fallibility. Therefore, responding to the issue to be more general, this article also suggests a proposal for a constitutional amendment to restructure the judicial review mechanism in accordance with the Canadian model known as, conceptually, judicial review with legislative finality. The recommendation aims to anticipate judicial error in constitutional interpretation as shown by the Constitutional Court Decision Number 14/PUU-XI/2013.